On the road to replacing invasive testing with cell‐based NIPT: Five clinical cases with aneuploidies, microduplication, unbalanced structural rearrangement, or mosaicism. (10th October 2017) - Vestergaard, Else Marie; Singh, Ripudaman; Schelde, Palle; Hatt, Lotte; Ravn, Katarina; Christensen, Rikke; Lildballe, Dorte Launholt; Petersen, Olav Bjørn; Uldbjerg, Niels; Vogel, Ida
Abstract: Objective: Trophoblastic fetal cells harvested from maternal blood have the capacity to be used for copy number analyses in a cell‐based non‐invasive prenatal test (cbNIPT). Potentially, this will result in increased resolution for detection of subchromosomal aberrations due to high quality DNA not intermixed with maternal DNA. We present 5 selected clinical cases from first trimester pregnancies where cbNIPT was used to demonstrate a wide range of clinically relevant aberrations. Method: Blood samples were collected from high risk pregnancies in gestational week 12 + 1 to 12 + 5. Fetal trophoblast cells were enriched and stained using fetal cell specific antibodies. The enriched cell fraction was scanned, and fetal cells were picked using a capillary‐based cell picking instrument. Subsequently, whole genome amplification (WGA) was performed on fetal cells, and the DNA was analyzed blindly by array comparative genomic hybridization (aCGH). Results: We present 5 cases where non‐invasive cell‐based prenatal test results are compared with aCGH results on chorionic villus samples (CVS), demonstrating aneuploidies including mosaicism, unbalanced translocations, subchromosomal deletions, or duplications. Conclusion: Aneuploidy and subchromosomal aberrations can be detected using fetal cells harvested from maternal blood. The method has the future potential of being offered as a cell‐based NIPT with large high genomic resolution. Abstract : What's already known about this topic? Enriched fetal cells from maternal blood can be used for performing whole genome amplification, followed by array CGH. What does this study add? cbNIPT can detect aneuploidy, microduplication, unbalanced structural rearrangements, and mosaic cases. cbNIPT can identify subchromosomal aberrations >10 Mb